2023
DOI: 10.1590/1518-8345.6107.3765
|View full text |Cite
|
Sign up to set email alerts
|

Serological and vaccine evaluation for hepatitis B among Community Health Workers

Abstract: Objective: to identify the vaccination and serological status against hepatitis B among community health workers; to vaccinate against hepatitis B virus and to evaluate the immune response of susceptible workers. Method: phase I, cross-sectional and descriptive study, among community health workers in a capital city of the Midwest region, through a self-administered questionnaire, checking of vaccination cards, and blood collection for testing of serological markers for hepatitis B. Phase II, cohort study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The study also found that community health education improved participants' attitudes towards vaccination and encouraged them to get vaccinated against hepatitis B. (Amaral, et al 2023) Similarly, a study in Iran found that community health education signi cantly improved participants' knowledge of hepatitis B and C transmission and prevention. The study also found that community health education improved participants' attitudes towards vaccination and their willingness to get vaccinated against hepatitis B.…”
Section: Literature Of Reviewmentioning
confidence: 87%
“…The study also found that community health education improved participants' attitudes towards vaccination and encouraged them to get vaccinated against hepatitis B. (Amaral, et al 2023) Similarly, a study in Iran found that community health education signi cantly improved participants' knowledge of hepatitis B and C transmission and prevention. The study also found that community health education improved participants' attitudes towards vaccination and their willingness to get vaccinated against hepatitis B.…”
Section: Literature Of Reviewmentioning
confidence: 87%
“…Although most workers were vaccinated and demonstrated an immunological response to hepatitis-B, susceptibility was found after one dose of vaccination (threat dose). 4 …”
Section: Introductionmentioning
confidence: 99%
“…Although most workers were vaccinated and demonstrated an immunological response to hepatitis-B, susceptibility was found after one dose of vaccination (threat dose). 4 There are differences in the literature on hepatitis-B immunity status and vaccinations. [5][6][7] In terms of immunization, extensive and detailed studies are needed due to vaccine procedures, administered doses, time differences, and application inadequacies.…”
Section: Introductionmentioning
confidence: 99%